Some grammatical complications of translation from English into Ukrainian (on the materials of information texts) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The peculiarities of translation some English grammatical constructions (passive voice, infinitive and participle) into Ukrainian are described. Grammatical transformations and factors influencing choice of translation variant are determined.
Keywords: translation; grammatical transformation; passive voice; infinitive; participle